The Qubit Fidelity Under Different Error Mechanisms Based on Error Correction Threshold - Li, Kai (Frontiers in Physics, 2022)
Quantum error correction is a crucial step to realize large-scale universal quantum computing, and the condition for realizing quantum error correction is that the error probability of each operation step must below some threshold. This requires that the qubits' quality and the quantum gates precision can reach a certain level experimentally. We firstly discuss the mechanism of quantum errors: the precision of quantum gates corresponds to unitary operator errors, and the quality of qubits is attributed to decoherence. Then, according to the threshold of the surface code error correction, we proved the minimum of quantum gate fidelity should not be less than 1-p with the error probability p, and found the natural decoherence time of qubits that can be used for error correction. This provides some kind of theoretical supports for qubits preparation and performing quantum operations experimentally.